Are Modified Gartland Type IV Supracondylar Humerus Fractures Different From Type III Fractures? A Retrospective Clinical Study - Duran Topak; İ̇smail Dere; Fatih Doğar; Burak Kuşçu; Ökkeş Bi̇lal (Acta Medica Alanya, 2020)
Aim: The present study investigates whether surgical treatment of modified Gartland Type IV supracondylar humerus fracture is radiologically and clinically different from the treatment of Type III fractures. Methods: The medical charts of 197 patients who underwent surgical treatment for pediatric supracondylar humerus fracture in our clinic between 2012 and 2015 were retrospectively reviewed, and 76 patients humerus Gartland Type III and unstable Type IV fractures regardless of neurovascular injury (49 males, 27 females) were included in the study as randomize. The patients were divided into two groups as patients with modified Gartland Type III (n=36) and patients with Type IV fractures (n=40). The mean age of the patients was 5.88±3.29 (1-15) years, and the mean duration of follow-up was 19.80±4.83 (12-29) months. All patients underwent surgery within the first 24 hours and closed reduction was first attempted. Posterior open reduction was performed in patients with failed attempts of closed reduction. The functional and cosmetic outcomes of the patients were evaluated according to the Flynn criteria. The Baumann’s angle was measured on the X-rays obtained in the last control visit.Results: The comparison of functional outcomes between the two groups revealed that satisfactory outcomes were obtained in 97.3% of patients in the Type III fracture group and 87.5% of patients in the Type IV fracture group; however, the difference was not statistically significant (p=0.509). The comparison of cosmetic outcomes showed that satisfactory outcomes have been obtained in 100% and 97.5% of the patients, and no significant difference was found between the two groups (p=0.495). There was no statistically significant difference between the two groups in terms of the need for open surgery, nerve injury, and Baumann’s angle (p=0.776, p=0.108, p=0.069, respectively).Conclusion: Modified Gartland Type IV pediatric supracondylar humerus fractures can be treated successfully just like Type III fractures with anatomical reduction, stable fixation and early initiation of joint movements.